INTELIGÊNCIA ARTIFICIAL: EQUILÍBRIO ENTRE O USO DE TECNOLOGIA E A MANUTENÇÃO DO VÍNCULO TERAPÊUTICO NA ENFERMAGEM (REMUNOM, 2025)
AbstractIntroduction: This article highlights the role of AI and its proposal as a complementary tool in daily nursing practice, with the most relevant aspects of the theme. General objective: To better describe how these new AI technologies can be used in nursing in comprehensive care, as a complementary tool. Method: It consists of an integrative literature review, with 10 (articles) selected from the last 5 (five) years, in the databases: LILACS, MEDLINE and BV SALUD. Results: The research findings reveal that the assistance of AI in nursing practice contributes to support, triage, monitoring and other nursing procedures, however, in a complementary way and not a substitute for human treatment. Discussion: Undeniably, the advancement of AI has been gradually growing in the area of health and nursing, which requires a greater balance between technology and humanized treatment, so that the care provided is effective, with quality and based on the process of humanization and ethical precepts. Conclusion: AI contributes several benefits to nursing practice, however, even with its benefits there is no possibility of promoting humanized treatment, therefore, the need for harmony between its use and the quality of human treatment is reflected, together with ethical precepts, a holistic view and the need for continuing education.Descriptors: Artificial intelligence in nursing. Human-technological balance. Humanized health interfaces.